Analysis of Workload and Social Support on Employee Performance (Survey on Employee Alfamart Subdistrict Warudoyong City Sukabumi) - Renaldy Sulaeman; Kokom Komariah; Resa Nurmala (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the extent of the influence of Workload and Social Support on Employee Performance at Alfamart in the Warudoyong District, Sukabumi City. The research method used is quantitative with a descriptive associative approach. This study employed simple random sampling technique. Data collection techniques involved observations and questionnaires distributed to 59 employees, containing statements related to the variables of workload, social support, and employee performance, measured using a Likert scale. The data obtained were subjected to various tests such as validity and reliability tests, as well US classical assumption tests, and were then analyzed using various tests with the help of SPSS 25 software to answer the hypotheses in this study. The results of the study indicate that workload and social support simultaneously affect employee performance. Partial testing shows that workload affects employee performance as the t-count of 3.605 is greater than the t-table of 1.672, and social support management affects employee performance as the t-count of 3.645 is greater than the t-table of 1.672. The findings of this research add to the understanding of developing strategies in managing employee performance by considering effective workload management in the retail environment.